Taxonomy, diversity, temporal and geographical distribution of Cutaneous Leishmaniasis in Colombia: A retrospective study (2016)
Leishmaniases are tropical zoonotic diseases, caused by kinetoplastid parasites from the genus Leishmania. New World (NW) species are related to sylvatic cycles although urbanization processes have been reported in some South American Countries such as Colombia. Currently, few studies show the relative distribution of Leishmania species related to cutaneous Leishmaniasis (CL) in South America due to the lack of accurate surveillance and public health systems. Herein, we conducted a systematic estimation of the Leishmania species causing CL in Colombia from 1980 to 2001 via molecular typing and isoenzymes. A total of 327 Leishmania isolates from humans, sandflies and reservoirs were typed as L. panamensis 61.3% (201), L. braziliensis 27.1% (88), L. lainsoni 0.6% (2), L. guyanensis 0.9% (3), L. infantum chagasi 4% (12), L. equatoriensis 0.6% (2), L. mexicana 2.1% (8), L. amazonensis 2.8% (9) and L. colombiensis 0.6% (2). This is the first report of two new Leishmania species circulating in Colombia and suggests the need to convince the Colombian government about the need to deploy and standardize tools for the species identification to provide adequate management to individuals suffering this pathology.